HUBUNGAN PENGETAHUAN MENSTRUASI DENGAN PERILAKU KESEHATAN REMAJA PUTRI - Setiawan, Juanita; Anggraeni, Haria; Ameliana, Mila; Romsilah, Neng (STIKES Permata Nusantara Cianjur, 2024)
The problem faced by young women, especially in developing countries, is a lack of knowledge about menstruation and menarche. This study aims to determine the relationship between menstrual knowledge and menstrual health behavior in adolescent girls at SMPN 1 Mande, Cianjur Regency. This study uses an analytical survey research design with a cross-sectional approach with 60 respondents. The results showed that 66.7% of female students had sufficient knowledge about menstruation, and 68.3% had good menstrual health behavior. There was a significant relationship between menstrual knowledge and adolescent girls' health behavior with a p-value of 0.000.